Changes in compound extremes of rainfall and temperature over West Africa using CMIP5 simulations. (1st October 2022) - Diba, Ibrahima; Diedhiou, Arona; Famien, Adjoua M; Camara, Moctar; Fotso-Nguemo, Thierry C
Abstract: This study aims to characterize changes in compound extremes of rainfall and temperature over West Africa. For this purpose, data from CHIRPS observations, the ERA5 reanalysis, and twenty-four (24) climate models involved in the CMIP5 Project were analyzed. First, climate models were evaluated in terms of their capacity to simulate summer mean climatology and compound extremes during the historical period (1981–2005), and secondly, changes in compound extremes were examined under RCP8.5 emission scenario between the near future (2031–2055) and the far future (2071–2095) relative to the historical period. Despite the presence of some biases, the ensemble mean of the models well reproduces the compound extremes patterns over West Africa at the seasonal and intraseasonal timescales. The analysis over the historical period with CHIRPS/ERA5 dataset shows a strong occurrence of the dry/warm mode over the northern Sahel during the June-July-August-September period (JJAS; main rainy season) and over the Guinean region during the February-March-April-May season (FMAM; first and main rainy season). These strong occurrences are due to a weak and highly frequent precipitation recorded in these zones. The compound wet/warm mode is frequent in JJAS over the Sahel and the Sudanian zone (transition area between Sahel and Guinean regions), while in FMAM, its occurrence is maximum over the Guinean region. The study also shows that the dry/warm mode will increase in the whole Sahel (western and central) and in the Guinean zone in the near and far futures while the compound wet/warm mode will decrease in the whole region. This study suggests that the West Africa region will be prone to drought intensified by warmer temperatures and calls for climate action and adaptation strategies to mitigate the risks on rain-fed agriculture, energy, and on animals and human health.